Validity of diagnostic codes to identify cases of severe acute liver injury in the U.S. Food and Drug Administration's Mini‐Sentinel Distributed Database. (25th June 2013) - Lo Re, Vincent; Haynes, Kevin; Goldberg, David; Forde, Kimberly A.; Carbonari, Dena M.; Leidl, Kimberly B. F.; Hennessy, Sean; Reddy, K. Rajender; Pawloski, Pamala A.; Daniel, Gregory W.; Cheetham, T. Craig; Iyer, Aarthi; et al.
ABSTRACT Purpose The validity of International Classification of Diseases, Ninth Revision, Clinical Modification (ICD‐9‐CM) codes to identify diagnoses of severe acute liver injury (SALI) is not well known. We examined the positive predictive values (PPVs) of hospital ICD‐9‐CM diagnoses in identifying SALI among health plan members in the Mini‐Sentinel Distributed Database (MSDD) for patients without liver/biliary disease and for those with chronic liver disease (CLD). Methods We selected random samples of members (149 without liver/biliary disease; 75 with CLD) with a principal hospital diagnosis suggestive of SALI (ICD‐9‐CM 570, 572.2, 572.4, 572.8, 573.3, 573.8, or V42.7) in the MSDD (2009–2010). Medical records were reviewed by hepatologists to confirm SALI events. PPVs of codes and code combinations for confirmed SALI were determined by CLD status. Results Among 105 members with available records and no liver/biliary disease, SALI was confirmed in 26 (PPV, 24.7%; 95%CI, 16.9−34.1%). Combined hospital diagnoses of acute hepatic necrosis (570) and liver disease sequelae (572.8) had high PPV (100%; 95%CI, 59.0–100%) and identified 7/26 (26.9%) events. Among 46 CLD members with available records, SALI was confirmed in 19 (PPV, 41.3%; 95%CI, 27.0–56.8%). Acute hepatic necrosis (570) or hepatorenal syndrome (572.4) plus any other SALI code had a PPV of 83.3% (95%CI, 51.6–97.9%) and identified 10/19 (52.6%) events. Conclusions Most individual hospital ICD‐9‐CM diagnoses had low PPV for confirmed SALI events. Select code combinations had high PPV but did not capture all events. Copyright © 2013 John Wiley & Sons, Ltd.